The Decade the 1990 in Mapuche History: Rebellion and Autonomy at the Center of the Debate (1989-1998); [la Década de 1990 en la Historia Mapuche: Rebelión y Autonomía en el Centro del Debate (1989-1998)] - Canales-Tapia, P; Escudero-Quiroz, F (Universidad Bernardo O Higgins, 2024)
The objective of this work is to analyze the Mapuche historical situation between 1989 and 1998, in order to identify the trajectories of the Mapuche movement and describe the circulation of ideas within this movement and in its dialogue with the state and Chilean society. in general. Thus, the methodology and theoretical scheme that support this proposal are based on the historical method, discourse analysis and debates around political action and autonomous processes, which allow us to glimpse the processes that began to emerge in this decade. © 2024 Universidad Bernardo O Higgins. All rights reserved.